Analysis of the Role of Islamic Banks in Promoting Green Finance in West Sumatra (Realization of SDGs 8 Point 10) - Putri Amelia; Yenty Astarie Dewi (Peneliti.net, 2026)
This study addresses air and environmental pollution, two significant economic issues for the long-term viability of businesses. Policymakers must prioritize green vision in economic growth now. In line with the tenets of maqasid sharia, sharia banking plays a significant role in fostering the development of green finance, which may motivate businesses to give environmental management greater attention. The purpose of this study is to provide a valuable addition to the body of knowledge on green finance and sustainable sharia banking, particularly in the context of Islamic banking. In order to fully understand sharia banking practices that prioritize sustainability and their effects on green financing, this study employs a qualitative and descriptive methodology. Three sharia banks that regularly publish reports—BSI, Bank Bukopin Syariah, and Bank Muamalat Indonesia—were the subjects of the study, which used library research as a methodology in the years 2021–2023. The findings of the study demonstrate the three sharia banks in West Sumatra's dedication to promoting sustainability via eco-friendly lending and involvement in several environmental projects. However, when using green financing, a number of institutions, such as Bank Muamalat and Bank Bukopin Syariah, see variations in their financial performance.